Integrative model for disclosing the diagnosis to children and adolescents with HIV in San Luis Potosí - Rubén Romero Ortiz; Ismael García Cedillo; Rocío Angélica González-Romo (Medisur)
Foundation: one of the greatest difficulties in caring for children and adolescents living with the acquired immunodeficiency virus is that they are unaware of their condition or are the last to know their health status because it is kept secret by primary caregivers and health personnel. Objective: to design and control an integrative model for disclosing the diagnosis to children and adolescents with acquired immunodeficiency virus/AIDS. Methods: psychoeducational, cognitive behavioral, and art therapy strategies were used. Three members of the medical staff, two primary caregivers, and two patients aged 13 and 14 living with HIV participated in the pilot application of this program. A pre-post quasi-experimental study was conducted. Results: In the post-assessment, it was found that adolescents were able to express emotions of anger and sadness, strengthened their support networks, decreased their anxiety level, and increased their knowledge about HIV/AIDS. Primary caregivers increased their knowledge about HIV/AIDS, although they expressed uncertainty about how infected children and adolescents might react in the future. Medical staff strengthened the relationship with primary caregivers and mentioned that the topic of sexuality was not addressed in the program. Conclusions: The program allows the diagnosis to be disclosed in a comprehensive and safe manner, and improves communication between primary caregivers, patients, and health personnel.